Trends in Glaucoma Medication Expenditures under Universal Health Coverage: A National Population-Based Longitudinal Survey in Taiwan - Shin-Lin Chiu; Chiao-Lee Chu; Chih-Hsin Muo; Chiu-Liang Chen; Shou-Jen Lan (Journal of Ophthalmology)
Medical care in Taiwan is well known for its low cost, high efficiency, high quality, excellent medical accessibility, and high equity. We investigate the trends in medication expenditures for glaucoma from 1997 to 2010. The results show that higher medical expenditures were incurred by patients who were aged ≥40 years, male patients, and patients in the highest salary population whereas lower medical expenditures were incurred by blue-collar workers. The medications with the most significant increases in expenditure were prostaglandin analogs (PGAs), α-agonists, and fixed combinations, whereas the medications with the most significant decreases in expenditure were β-blockers and cholinergic agonists. The number of trabeculectomies shows two downward break points in 1999 and 2000 when PGAs were listed and were reimbursed. These results suggest socioeconomic disparities in glaucoma care, as well as understanding of the changes in the expenditure of glaucoma medications under such universal health insurance coverage system.